Implant Composed of Demineralized Bone and Mesenchymal Stem Cells Genetically Modified with AdBMP2/AdBMP7 for the Regeneration of Bone Fractures in Ovis aries. (13th October 2016) - Hernandez-Hurtado, Adelina A.; Borrego-Soto, Gissela; Marino-Martinez, Ivan A.; Lara-Arias, Jorge; Romero-Diaz, Viktor J.; Abrego-Guerra, Adalberto; Vilchez-Cavazos, Jose F.; Elizondo-Riojas, Guillermo; Martinez-Rodriguez, Herminia G.; Espinoza-Juarez, Marcela A.; Lopez-Romero, Gloria C.; Robles-Zamora, Alejandro; et al.
Abstract : Adipose-derived mesenchymal stem cells (ADMSCs) are inducible to an osteogenic phenotype by the bone morphogenetic proteins (BMPs). This facilitates the generation of implants for bone tissue regeneration. This study evaluated the in vitro osteogenic differentiation of ADMSCs transduced individually and in combination with adenoviral vectors expressing BMP2 and BMP7. Moreover, the effectiveness of the implant containing ADMSCs transduced with the adenoviral vectors AdBMP2/AdBMP7 and embedded in demineralized bone matrix (DBM) was tested in a model of tibial fracture in sheep. This graft was compared to ewes implanted with untransduced ADMSCs embedded in the same matrix and with injured but untreated animals. In vivo results showed accelerated osteogenesis in the group treated with the AdBMP2/AdBMP7 transduced ADMSC graft, which also showed improved restoration of the normal bone morphology.